A Government Policy in Determining the Regional Boundaries Between Lima Puluh Kota Regency and Payakumbuh City, West Sumatra - Jery Mihardi; Afriva Khaidir (Universitas Bengkulu, 2021)
This research is based on Regulation of the Minister of Home Affairs Number 76 of 2012 concerning on Guidelines for Boundary Confirmation and Regulation of the Minister of Home Affairs Number 141 of 2017 concerning on Regional Boundaries. This research method was a descriptive analysis with a triangulation method and a triangulation of sources for testing the data of this research. The data of this research were analyzed by using a SWOT analysis. The results of this research revealed that S-O Strategy (1) Clarifying the boundaries between the two Local Governments in realizing a clear government administration; (2) Optimizing the role of the Community in Realizing the Development with the clear territorial boundaries; W-O Strategy (1) Coordinating with related parties to realize the good government administration services; (2) There is guidance and supervision to the Regional Government through the Provincial Government and the Central Government; S-T Strategy (1) Building the government cooperation by taking an agreement through the Provincial Government; (2) Building the good communication with the community at every deliberation; W-T Strategy (1) Strengthening the regulations by disseminating every decision from the Ministry of Home Affairs; (2) Mediating every meeting through the conflicting parties.